Place avoidance tasks as tools in the behavioral neuroscience of learning and memory - Stuchlík, A; Petrásek, T; Prokopová, I; Holubová, K; Hatalová, H; Valeš, K; Kubík, S; Dockery, C; Wesierska, M (Physiological research, 2013)
Spatial navigation comprises a widely-studied complex of animal behaviors. Its study offers many methodological advantages over other approaches, enabling assessment of a variety of experimental questions and the possibility to compare the results across different species. Spatial navigation in laboratory animals is often considered a model of higher human cognitive functions including declarative memory. Almost fifteen years ago, a novel dry-arena task for rodents was designed in our laboratory, originally named the place avoidance task, and later a modification of this approach was established and called active place avoidance task. It employs a continuously rotating arena, upon which animals are trained to avoid a stable sector defined according to room-frame coordinates. This review describes the development of the place avoidance tasks, evaluates the cognitive processes associated with performance and explores the application of place avoidance in the testing of spatial learning after neuropharmacological, lesion and other experimental manipulations.
Keywords: kognice; modely u zvířat; Cognition; Neurosciences; neurovědy; vnímání prostoru; Memory; chování zvířat; Spatial Behavior; Species Specificity; prostorové chování; druhová specificita; paměť; Models, Animal; Space Perception; zvířata; Animals; Behavioral Research; Avoidance Learning; Behavior, Animal; behaviorální výzkum; učení vyhýbat se